2020
DOI: 10.1088/1755-1315/500/1/012081
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of atmospheric correction algorithms for Sentinel-2 over paddy field area

Abstract: Atmospheric correction is essential in satellite data processing to reduce atmospheric and lighting effects by studying the physical parameter of the earth’s surface. In this study, ATCOR and 6S algorithms were evaluated for Sentinel-2 over paddy field area. In this evaluation, level-1C Top of Atmosphere (TOA) Sentinel-2 image was used as an input data. The spectral pattern analysis of the results was used to assess the reliability of the methods. As a result, the both methods produced the correct spectral pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
0
0
Order By: Relevance
“…algorithm (Ulfa et al, 2020), and Cianjur and Klaten regency using DOS and 6S atmospheres correction methods (F. Muchsin, Supriyatna, Harmoko, & Prasasti, 2022). The results showed that the 6S model had better accuracy for the spectral response of the rice plant phase compared to the DOS model.…”
Section: Discussionmentioning
confidence: 99%
“…algorithm (Ulfa et al, 2020), and Cianjur and Klaten regency using DOS and 6S atmospheres correction methods (F. Muchsin, Supriyatna, Harmoko, & Prasasti, 2022). The results showed that the 6S model had better accuracy for the spectral response of the rice plant phase compared to the DOS model.…”
Section: Discussionmentioning
confidence: 99%